2020
DOI: 10.1051/e3sconf/202014602001
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-functionalized silica nanoparticles for improving water flood sweep efficiency in Berea sandstones

Abstract: Extraction of oil trapped after primary and secondary oil production stages still poses many challenges in the oil industry. Therefore, innovative enhanced oil recovery (EOR) technologies are required to run the production more economically. Recent advances suggest renewed application of surfacefunctionalized nanoparticles (NPs) for oil recovery due to improved stability and solubility, stabilization of emulsions, and low retention on porous media. The improved surface properties make the NPs more appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…The authors associated the EOR effect to the NPs’ ability to decrease the injection pressure; the authors argued that displacement pressure decrease is related to the formation of a wedge film between the oil and the rock surface. More recently, Bila et al [ 15 , 16 ], Bila and Torsæter [ 17 ] carried out a series of flooding experiments with polymer-coated SiO NPs in Berea sandstone core plugs. Their studies revealed an incremental recovery ranging from 2.6% to 14% of the OOIP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors associated the EOR effect to the NPs’ ability to decrease the injection pressure; the authors argued that displacement pressure decrease is related to the formation of a wedge film between the oil and the rock surface. More recently, Bila et al [ 15 , 16 ], Bila and Torsæter [ 17 ] carried out a series of flooding experiments with polymer-coated SiO NPs in Berea sandstone core plugs. Their studies revealed an incremental recovery ranging from 2.6% to 14% of the OOIP.…”
Section: Introductionmentioning
confidence: 99%
“…This work aims to expand our previous works [ 15 , 16 ] and attempts to investigate the recovery mechanisms of polymer-coated silica NPs under harsh reservoir conditions of high temperature and salinity. The goal is to provide additional experimental results to the data bank on the nanoparticles for enhanced oil recovery projects, while paving the way to improve our understanding of the underlying EOR mechanisms associated with silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Hendraningrat and Torsaeter [13] used a water-soluble polymer, polyvinylpyrrolidone (PVP), to stabilize silica-based nanofluids and attained an increment of 2% of the OOIP. More recently, a series of flooding experiments using polymer-coated silica NPs dispersed in seawater to 0.1 wt.% was carried out by Bila et al [16] and Bila et al [17]. The authors reported an increase in oil recovery of about 14% of the OOIP in water-wet Berea core plugs and 5% of the OOIP in neutral-wet cores, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Their flooding experiments revealed an increment of 2% of the OOIP. A series of flooding experiments for EOR by means of polymer-coated silica NPs dispersed in seawater to 0.1wt.% were recently carried out by Bila, et al [16] and Bila, et al [17]. They reported an increase in oil recovery of about 14% of the OOIP in water-wet Berea core plugs and 5% of the OOIP in neutral-wet cores, respectively.…”
Section: Introductionmentioning
confidence: 99%